2000
DOI: 10.1097/00005373-200001000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Occult Hypoperfusion Is Associated with a Significant Increase in Infection Rate and Mortality in Major Trauma Patients

Abstract: A clear increase in infections occurred in patients with OH whose lactate levels did not correct by 12 hours, with an associated increase in length of stay, days in surgical/trauma intensive care unit, hospital charges, and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
3
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(133 citation statements)
references
References 37 publications
6
119
3
5
Order By: Relevance
“…There was a significant relation between mean age and mortality (p=0.008). Mean (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) hours in the HL group. There was a significant relation between increased MVD and mortality (p=0.006).…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant relation between mean age and mortality (p=0.008). Mean (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) hours in the HL group. There was a significant relation between increased MVD and mortality (p=0.006).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our study, Shapiro et al [8] with 1278 patients demonstrated that increasing lactate levels were associated with increased mortality in the patients presenting with sepsis. Sustained high lactate levels in ICU patients demonstrated by serial measurements have shown to be predictive of in hospital mortality [9][10][11] Nichol AD et al in their study concluded that In critically ill patients, relative hyperlactataemia is independently associated with increased hospital mortality. Blood lactate concentrations > 0.75 mmol.L-1 can be used by clinicians to identify patients at higher risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent hyperlactatemia is considered to reflect occult hypoperfusion and has been associated with poor outcomes in trauma [32], cardiac arrest [33] and high-risk surgery [34].…”
Section: Lactate Clearancementioning
confidence: 99%